2009
DOI: 10.1111/j.1365-2516.2009.02072.x
|View full text |Cite
|
Sign up to set email alerts
|

Gynaecological and obstetrical problems in women with different bleeding disorders

Abstract: The aim of this case-control study was to analyse the prevalence of gynaecological, obstetrical and other more general bleeding symptoms in 114 women affected by various inherited bleeding disorders, who were compared with 114 apparently healthy women. Retrospective information were collected by means of two specific questionnaires, one on gynaecological and obstetrical bleeding symptoms, with special focus on the presence of menorrhagia as defined by a pictorial blood loss assessment chart (PBAC); and the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 39 publications
2
37
1
1
Order By: Relevance
“…The incidence of primary PPH was 44% in our study group, thus higher than what has been described in the previous studies where similar methods of data collection were used, and similar to the reported incidence in studies investigating PPH by patient recall [2, 18, 20, 2224, 38]. …”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The incidence of primary PPH was 44% in our study group, thus higher than what has been described in the previous studies where similar methods of data collection were used, and similar to the reported incidence in studies investigating PPH by patient recall [2, 18, 20, 2224, 38]. …”
Section: Discussionsupporting
confidence: 85%
“…Studies using interviews and questionnaires for data collection have reported a primary PPH incidence of 31–59% [2, 18, 20, 22, 23], whereas the incidence was 15–34% in studies using an objective measure of blood loss (>500 ml) and medical records for data collection [2, 24, 38, 39]. However, comparing the results between these studies is problematic, as the study groups may differ regarding severity of VWD, hemostatic drug treatment and obstetric care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…a porodem, obserwuje się w przypadku 2-5% wszystkich ciąż [11]. Częstość występowania APH wśród nosicielek hemofilii oraz w populacji ogólnej jest porównywalna [12,14]. W większości przypadków APH to następstwo patologii łożyska -występowania łożyska przodującego lub jego przedwczesnego odklejenia.…”
Section: Opieka W Czasie Ciążyunclassified
“…Due to increasing factor concentrations with developing pregnancy, patients with von Willebrand disease (type I) or haemophilia (only A, as factor IX does not increase) do not have an elevated bleeding risk during pregnancy compared to healthy ones. Nevertheless, this risk is greatly augmented in the postpartum period [17,23,24].…”
Section: Definition Risk Factors and Preparationmentioning
confidence: 99%